‘Jewish culture is inseparable from the struggle against reaction’: forging an Australian Jewish antifascist culture in the 1940s - Kaiser, Max (Fascism, 2020)
In the immediate postwar period Jewish communities worldwide sought to draw political lessons from the events of the Holocaust, the rise of fascism and the Second World War. A distinctive popular Jewish left antifascist politics developed as a way of memorialising the Holocaust, struggling against antisemitism and developing anti-racist and anti-assimilationist Jewish cultures. This article looks at the trilingual magazine Jewish Youth, published in Melbourne in the 1940s in English, Yiddish and Hebrew, as a prism through which to examine Jewish antifascist culture in Australia. Jewish Youth featured an oppositional political stance against antisemitism and fascism, tied often to Holocaust memorialisation; a conscious political and cultural minoritarianism and resistance to assimilation; and a certain fluctuating multilingualism, tied to its transnational situatedness and plurality of audiences.